Anne d'Alençon y Margherita Paleologo: Mujeres gobernantes entre la esfera pública y la privada. - SIRVENT, ALEJANDRA MARTÍNEZ; ANDOLFATO, ANNA MARIA (Scripta, 2014)
The ladies of the Renaissance Courts, besides carrying out with their responsibilities like daughters, wives and mothers, also took an active part in the political life of their territories. Some of them, in absence of their husbands, had to take responsibility of the Regency. Their active involvement in the government issues, as well as their feelings, is seen on the correspondence which they kept with the diverse authorities. The letters of Anne d'Alençon and her daughter Margherita Paleologo with Antoine Perrenot de Granvela, State secretary of the Emperor Charles V, allowed us to study how the private and public spheres melted together in their correspondence as well as the act of writing is the vehicle to take part with when it is necessary.